Forecasting the Effects of Failure Criteria in Assessing Ship Structural Damage Modes - Aditya Rio Prabowo; R. Ridwan; T. Tuswan; Fitrian Imaduddin (Civil Engineering Journal, 2022)
The failure to achieve satisfactory results will cause immense losses in major projects. Nevertheless, the modeling limitations and phenomenon assumptions represented by failure criteria can significantly influence the final results—e.g., the damage mode, affecting its quantification—thus representing an interesting topic for technical assessment. This work aims to forecast the effects of several failure criteria on the damage occurring due to structural loading schemes, such as compression, torsion, and tensile tests. Failure criteria are taken based on the proposal of pioneer researchers and include those of Peschmann (P), Germanischer Lloyd (GL), Liu (LIU), and Rice–Tracey and Cockroft–Latham (RTCL). A series of nonlinear finite element analyses (NLFEA) are conducted by inputting these criteria into different loading schemes. To obtain reliable validation, the proposed models are designed based on previous laboratory experiments. The numerical results of NLFEA in the forms of damage mode, i.e., tearing, plastic deformation, and torsion, are cross-checked with experimental data. The results show that numerical modeling using the LIU criterion produces slightly larger discrepancies compared with experimental data. This indication is founded on the analysis of stress–strain, load–displacement, and shear stress–strain during the tensile test, compressive load, and torsion load, respectively. According to this work, we formulate recommendations based on the forecast tendency and accuracy for each damage mode subjected to failure criteria. Therefore, future works can adopt the findings in our current work when choosing to apply specific criteria in structural modeling and load idealization. Doi: 10.28991/CEJ-2022-08-10-03 Full Text: PDF